Gateway Reflex and Mechanotransduction - Matsuyama, Shiina; Tanaka, Yuki; Hasebe, Rie; Hojyo, Shintaro; Murakami, Masaaki (Frontiers in Immunology, 2021)
The gateway reflex explains how autoreactive CD4+ T cells cause inflammation in tissues that have blood-barriers, such as the central nervous system and retina. It depends on neural activations in response to specific external stimuli, such as gravity, pain, stress, and light, which lead to the secretion of noradrenaline at specific vessels in the tissues. Noradrenaline activates NFB at these vessels, followed by an increase of chemokine expression as well as a reduction of tight junction molecules to accumulate autoreactive CD4+ T cells, which breach blood-barriers. Transient receptor potential vanilloid 1 (TRPV1) molecules on sensory neurons are critical for the gateway reflex, indicating the importance of mechano-sensing. In this review, we overview the gateway reflex with a special interest in mechanosensory transduction (mechanotransduction).